Prostate Cancer Diagnosis PSA, Biopsy and Beyond - Jones, J. Stephen; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2013)
Based on the highly successful first edition of Prostate Biopsy: Indications, Techniques, and Complications, this new volume presents new concepts that have emerged in answer to current questions from its audience. Many new perspectives and technologies are presented, many from the authors’ internationally recognized work on the topic. Substantial developments in techniques and complications are explored in detail. The chapter authors comprise a complete spectrum of specialists in their respective subject areas. All authors are internationally accepted as the premier authorities on their chosen topics. Prostate Cancer Diagnosis: PSA, Biopsy, and Beyond presents new data on the controversial issue of PSA screening and thresholds as indication to perform biopsy. Office based transrectal saturation biopsy is covered in detail. Other topics explored include template guided biopsy and image-guided biopsy as well as a completely new paradigm for prevention of complications. Prostate Cancer Diagnosis: PSA, Biopsy, and Beyond will be of great value and utility to all practicing urologists.  .
Ch.1: Defining the Problem -- Ch.2: Prostate Cancer Screening: Navigating the Controversy -- Ch.3: Is the PSA Era Over? -- Ch.4: PSA Dynamics -- Ch.5: Percent Free PSA -- Ch.6: PCA3 and other Urinary Markers -- Ch.7: Blood-Based Tumor Markers for Prostate Cancer -- Ch.8: Prediction Models in Prostate Cancer Diagnosis and Preparation for Biopsy -- Ch.9: Is There a Role for Medications to Reduce the Need for Prostate Biopsy? -- Ch.10: Indications For Initial Biopsy:  Is The PSA Threshold Over? -- Ch.11: Preparation for Prostate Biopsy -- Ch.12: Pain Prevention -- Ch.13: Prostate Biopsy -- Ch.14: Prostate Biopsy Techniques -- Ch.15: Transperineal Biopsy -- Ch.16: Pathological Implications of Prostate Biopsy -- Ch.17: Complications of Transrectal Ultrasound Guided Prostate Biopsy -- Ch.18: After the Biopsy: Management of High Grade Prostatic Intraepithelial Neoplasia (HGPIN) -- Ch.19: Atypical Small Acinar Proliferation -- Ch.20: Repeat Prostate Biopsy Strategies – Indications and Techniques -- Ch.21: Transperineal Mapping Biopsy of the Prostate for Assessment of the Minimal Risk Patient -- Ch.22: Management of the Patient Following a Negative Biopsy: Saturation Biopsy -- Ch.23: Role of imaging as an adjunct or replacement for biopsy: American Experience -- Ch.24: Role Of Imaging As An Adjunct Or Replacement For Biopsy: European Experience -- Ch.25: Prostate Cancer Detection: Lessons Learnt in the Cleveland Clinic Experience with Focus on the Negative Biopsy -- Ch.26: Future Directions in Prostate Cancer Diagnosis.
Keywords: Medicine; Oncology .; Medicine/Public Health, general; Oncology